Effect of Capital Structure to Profitability on Textile and Garment Industry Company Listed on The Indonesia Stock Exchange 2010-2012 - Rosmiaty Tarmizi; Allansyah Pratama (Universitas Bandar Lampung (UBL), 2015)
This study aims to identify and analyze the effect of capital structure on the proxied by DERto profitability in the proxy with the ROE. The hypothesis is Debt to Equity Ratio significant effect on return on equity in the companies listed in Indonesia Stock Exchange. The sample in this study is the subsectors textile and garment are listed in Indonesia Stock Exchange in2010-2012. Sampling using purposive sampling so obtained a total sample of 15 textile and garment companies that meet the criteria for the study sample that has been set. Capital structure measured by DER, while profitability is measured by ROE. Hypothesis testing using simple linear regression analysis using SPSS 18.0 for windows. The results showed that partially DER significant negative effect on ROE textile and garment manufacturing companies listed in Indonesia Stock Exchange.